Terms implied by Courts: a comparative appraisal of the law in Malaysia, the United Kingdom and Australia - Shair Mohamed, Mohd. Akram (2014)
The normal contract is not an isolated act, but an incident in the conduct of business or in the context of some more general relation such that of landlord and tenant or employer-employee. It will be usually set against a background of usage. In addition, therefore to the terms which the parties have expressly adopted there may be other imported into the contract from its contexts. The implications may be derived from custom or rest upon statute, or may be inferred by the judges to reinforce the language of the parties and realise their manifest intention. Thus addition to terms imported into particular type of contract, the court may in any class of contract, imply a term in order to repair an intrinsic failure of expression. The document which the parties have prepared may leave no doubt as to the general ambit of their obligations; but they may have omitted, through inadvertence or clumsy draftsmanship, to cover an incidental contingency, unless remedied, may negative their design. In such a case the judge may himself supply a further term, which will implement their presumed intention, and give „business efficacy‟ to their contract. In doing so he purports at least to do merely. What the parties would have done themselves, had they thought of the matter. The assertion of this judicial power to imply terms has been asserted by the courts first utilising the business efficacy test, the officious bystander test, both the combined tests, and latterly through the Privy Council‟s judicial eyes, reasonableness and equitable tests. This paper briefly conducts a critical appraisal of the tests in England, Malaysia and Australia.